LiCs3AlB7O14: achieving enhanced optical anisotropy via [AlO4] tetrahedron introduction to rearrange the anionic framework. Issue 13 (15th March 2023) - Li, Xingqi; Chu, Dongdong; Qiu, Haotian; Wu, Yabo; Hou, Xueling
Abstract : Herein, by introducing [AlO4 ] tetrahedra, a new aluminoborate was discovered. This work confirms that the introduction of [AlO4 ] tetrahedra can lead to the rearrangement of anionic framework of borate system and thereby enhance the birefringence. Abstract : Borate has become a hot topic because of its rich structural chemistry and excellent properties for functional materials fields. The rearrangement of π-conjugated B–O units is key to enhancing the optical anisotropy, but it remains a challenge. Herein, by introducing [AlO4 ] tetrahedra, a new congruent melting aluminoborate LiCs3 AlB7 O14 with [B7 O14 ] clusters was discovered. This work confirms that the introduction of [AlO4 ] tetrahedra can lead to the rearrangement of anionic framework of the borate system and thereby enhance the birefringence of LiCs3 AlB7 O14 . The birefringence is about 4.1 times higher than that of its congener Li4 Cs3 B7 O14 with the same [B7 O14 ] clusters. Similarly, the effects of [AlO4 ] tetrahedra on the rearrangement of the B–O anionic framework are also demonstrated in other known borates.